Monotheism and the rise of science - Schellenberg, J. L. (Cambridge elements. Elements in religion and monotheism, 2020)
This Element traces the effects of science's rise on the cultural status of monotheism. Starting in the past, it shows how monotheism contributed to science's rise, and how, returning the favour, science provided aid and support, until fairly recently, for the continuing success of monotheism in the west. Turning to the present, the Element explores reasons for supposing that explanatorily, and even on an existential level, science is taking over monotheism's traditional roles in western culture. These reasons are found to be less powerful than is commonly supposed, though the existential challenge can be made effective when framed in an unusual and indirect manner. Finally, the Element considers how the relationship between science's high standing and the status of monotheism might appear in the future. Could something like monotheism rise again, and might science help it do so? The Element concludes that an affirmative answer is possible.